2010
DOI: 10.1007/s11274-010-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacterial species on Lippia multiflora herbal tea leaves and the influence of steam pasteurization

Abstract: The consumption of herbal teas is an increasing phenomenon among tea consumers globally. Some of these herbal teas are not pre-treated to reduce their microbial load before consumption, and thus constitute a health risk to consumers. In this study, the effect of steam pasteurization, at [99°C for 2.5 min, on the microbial load of Lippia multiflora herbal tea leaves was evaluated. Microbial enumeration was conducted on potato dextrose agar, plate count agar, violet red bile agar, yeast peptone dextrose agar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A recent initiative to commercialise African plants for international markets has targeted L. multiflora for development. Under this initiative, steam pasteurisation of the dry leaves has been investigated to control microbial loads on the tea (Arthur, Cameron, Joubert, & Witthuhn, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent initiative to commercialise African plants for international markets has targeted L. multiflora for development. Under this initiative, steam pasteurisation of the dry leaves has been investigated to control microbial loads on the tea (Arthur, Cameron, Joubert, & Witthuhn, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that herbs need boiling water for brewing, because water with lower temperature cause an increase in the number of microorganisms of the brewing. Arthur et al (2011) evaluated steam pasteurization and temperature treatments (99 °C for 5 min) on the microbial load of Lippia multiflora leaves. Results showed that pasteurization treatments reduced the microbial load and no Coliform was observed.…”
Section: Resultsmentioning
confidence: 99%